Monitoring underground nuclear explosions - Dahlman, Ola; Israelson, Hans (Elsevier Scientific Pub. Co. ; Distributors for the U.S. and Canada, Elsevier/North-Holland, 1977)
Monitoring Underground Nuclear Explosions.